Changes in Physical Performance in Older Women According to Presence and Treatment of Diabetes Mellitus. Issue 11 (28th October 2013) - Lee, Christine G.; Schwartz, Ann V.; Yaffe, Kristine; Hillier, Teresa A.; LeBlanc, Erin S.; Cawthon, Peggy M.; the Study of Osteoporotic Fractures Research Group
<x xml:space="preserve">Abstract</x> Objectives To determine whether older women with diabetes mellitus have a greater longitudinal decline in physical performance than those without and whether any decline differs according to insulin sensitizer use. Design Prospective cohort study. Setting Baltimore, Maryland; Minneapolis, Minnesota; Portland, Oregon; and the Monongahela, Pennsylvania. Participants Community‐dwelling women (mean age 78.5 ± 3.6) enrolled in the Study of Osteoporotic Fractures in 1997–98 and restudied 4.9 ± 0.6 years later (N = 2, 864). Measurements Women were categorized as having no diabetes mellitus (n = 2, 680) or having diabetes mellitus (n = 184). A prescription medication inventory was used to determine use of insulin sensitizers (metformin and thiazolidinedione). The outcomes were longitudinal changes in physical performance measures, including grip strength, usual walk speed, and rapid walk speed. Results Estimates from fully adjusted models showed that women with diabetes mellitus had greater declines in usual walk speed (−0.16 m/s, 95% confidence interval (CI) = −0.19 to −0.14) and rapid walk speed (−0.21 m/s, 95% CI = −0.24 to −0.17) than those without (usual walk speed −0.11 m/s, 95% CI = −0.12 to −0.11, P < .001; rapid walk speed −0.15 m/s, 95% CI = −0.16 to −0.14; P = .005). Women with diabetes mellitus taking insulin sensitizers had less decline in usual walk speed than those not taking insulin sensitizers (P < .001). Declines in grip strength did not differ significantly by diabetes mellitus status or insulin sensitizer use. Conclusion Older women with diabetes mellitus have a greater decline in walk speed, but not grip strength, than older women without diabetes mellitus. Clinical studies in older adults to determine whether diabetes mellitus treatments such as insulin sensitizers can prevent loss in walk speed and mobility are needed.